2018
DOI: 10.1017/jgc.2018.3
|View full text |Cite
|
Sign up to set email alerts
|

The Psychometric Properties of the Counselor Burnout Inventory in Greek School Counsellors

Abstract: The present study aimed at testing and exploring the psychometric properties of the Counselor Burnout Inventory (CBI) in Greek school counsellors. Two hundred school counsellors from all over Greece participated in the study. The confirmatory study revealed four dimensions of the Greek version of CBI; namely, exhaustion, deterioration in personal life, incompetence, and negative work environment. Adequate psychometric properties of the version were revealed as well. The results also showed a negative relation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The degree to which professionals experienced occupational burnout was measured by the counselor burnout inventory (CBI) [ 34 ], validated by Kounenou et al [ 35 ], for which the participants had to state the frequency with which they encounter burnout on a 5-point scale (1 = “never” to 5 = “always”). It includes 20 items (e.g., “I feel exhausted due to my work as a counselor/therapist”).…”
Section: Methodsmentioning
confidence: 99%
“…The degree to which professionals experienced occupational burnout was measured by the counselor burnout inventory (CBI) [ 34 ], validated by Kounenou et al [ 35 ], for which the participants had to state the frequency with which they encounter burnout on a 5-point scale (1 = “never” to 5 = “always”). It includes 20 items (e.g., “I feel exhausted due to my work as a counselor/therapist”).…”
Section: Methodsmentioning
confidence: 99%
“…Professional learning opportunities contribute positively to an individual's self-efficacy. A study of 180 Greek school career counselors found counselors showed higher confidence, felt empowered after having adequate training access and opportunities, and as a result, it increased their professional efficacy and competencies (Kounenou et al, 2010(Kounenou et al, , 2018. Additionally, programs such as counseling preparation programs or continuous professional training attended by counselors, too, increased their self-efficacy (Malkoç and Sünbül, 2020;Perry et al, 2020).…”
Section: Access To Training Perceived Supervisor Support Of Training and Counseling Self-efficacymentioning
confidence: 99%